PENERAPAN PENDIDIKAN KARAKTER PADA SISWA KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN SMK NEGERI 2 SURAKARTA - Hasanah, Fatmawati Nur (Jurnal Nosel, 2012)
The purpose of this study was to know about: (1) implementation of character education on student of Skills Competency Light Vehicle Engineering SMK Negeri 2 Surakarta; (2) the results of implementation of character education on student of Skills Competency Light Vehicle Engineering SMK Negeri 2 Surakarta. This research used descriptive qualitative method and the design used single case study at SMK Negeri 2 Surakarta. Research subjects were students of Skills Competency Light Vehicle Engineering SMK Negeri 2 Surakarta, as many as 316 students. The research sample as many as 11 students for interview and 87 for questionnaire. Sampling technique was purposive sampling. Data collection techniques used were questionnaire, interview, observation, and documentary method. Testing of the validity instrument was conducted based on the Pearson's Product Moment Correlation. Reliability test instrument used Cronbach's Alpha. The result of this research were: (1) Principal, Vice Principal of Academy Field, Vice Principal of Studentships Field, Vice Principal of Human Resource Development, Vice Principal of School Public Relations Field, Guidance Counselor Teachers and Productive Teachers of Skill Competency Light Vehicle Engineering SMK Negeri 2 Surakarta has implemented a character education systematically to students, especially students of Skill Competency Light Vehicle Engineering, which is a lesson plans and syllabus; (2) implementation of character education is also conducted continuously by the teacher SMK Negeri 2 Surakarta in the form of 3S Program, the training and education of VEDC Malang, P3G Bandung, P4TK Bandung and from the Provincial of Central Java; (3) implementation of character education through co-curricular activities and extracurricular; (4) results showed that students' character of Skill Competency Light Vehicle Engineering SMK Negeri 2 Surakarta average is 77.46%. Students of Skill Competency Light Vehicle Engineering SMK Negeri 2 Surakarta has good character. In addition, there are students who have not been well characterized because it is not strong in having some of the main characters, such as Responsibility and Self-Discipline characters; (5) condition students of Skill Competency Light Vehicle Engineering SMK Negeri 2 Surakarta who do not already have eight main characters have a low level of discipline, lack of initiative, lack of responsibility, and lack of respect for others; (6) condition students of Skill Competency Light Vehicle Engineering SMK Negeri 2 Surakarta which has eight main characters are more disciplined, have initiative, responsible, helpful and growing affection, respect for others and good at gratitude.